Biochemical Profile of Selected Normal Healthy Adult Men and Women - Vijayalakshmi, P.; Rema, S. R. (The Indian Journal of Nutrition and Dietetics, 1994)
Adequate data is available in the developed and developing nations with reference to anthropometric measurements and food intake for the assessment of the nutritional status of adults. However such organised data Is not available for our country with special reference to biochemical profile, where there may be a wide variation arising out of the environmental, socioeconomic, racial and cultural and dietary factors. The present study was undertaken to determine the biochemical profile of selected healthy adult men and women, with reference to selected metabolites and nutrients and compare the same with values obtained in developed countries, so that a beginning can be made towards arriving at guideline values for biochemical profile of Indians.